The effects of fibre contents on the tensile strength and surface morphology of high density polyethylene/palm pressed fibre biocomposite film - Aris, Noor Fatheyah (2014)
Palm pressed fibre (PPF) with particle size of 200 micron was utilized as a filler to produce environment friendly biocomposite film. PPF contains 5-6% oil residue after the oil extraction process and the oil can be used as a lubricant to assist the distribution of PPF throughout the matrix of plastic resin during processing. In this study, high density polyethylene (HDPE) plastic resin was incorporated with untreated PPF at four different weight percentages namely, 5, 10, 15 and 20 wt%. Each mixture was compounded via twin screw extruder prior to compression moulding into film sheets with thickness of 0.15mm. Maleic anhydride (MAH) and glycerol were used as compatibilizer and plasticizing agents. The effect of PPF loading on the tensile strength and the surface morphology were the main interest. It was found that by increasing the PPF contents had increased the stiffness of the films but reduced the tensile strength and elongation at break due to weak interfacial adhesion between HDPE matrix and PPF. This was probably due to insufficient amount of MAH to compatabilize the increasing amount of PPF, thus resulting non-uniform PPF distribution across the HDPE matrix. The findings were supported by SEM micrographs which showed rough surface and the disruption of the continuous phase of HDPE matrix, thus weakening the strength and flexibility of the samples. HDPE/PPF biocomposite has a potential to be used in agriculture sectors such as mulching film.